Comparison of bupivacaine with fentanyl and bupivacaine with butorphanol for brachial plexus block by axillary approach- a prospective, double blind, randomized study - Kapse, Upendrakumar S.; Bhalerao, Pradnya M. (International Journal of Research in Medical Sciences, 2017)
Background: Brachial plexus block by axillary approach achieves good motor sensory and sympathetic blockade below elbow joint. Addition of opioid compounds to local anesthetics improves the block properties and reduces central opioid related side effects. We compared combination of local anaesthetic bupivacaine with fentanyl and butorphanol in axillary block for upper limb surgeries. Aims and objectives were to compare the block quality, duration of sensory and motor block, post-operative analgesia, safety and side effects in two groups. Methods: 60 patients posted for elective or emergency forearm and hand surgeries were randomly divided into 2 groups of 30 each. group B (n=30) received 40ml of 0.25% bupivacaine with butorphanol (25mcg/kg) and group F (n=30) received 40ml of 0.25% bupicaine with fentanyl (1mcg/kg). Onset and duration of sensory block (pinprick) and motor block (Lovett’s rating scale), hemodynamic parameters, postoperative analgesia and side effects were noted in each group. Results: The mean time of onset of sensory block was earlier in group B (2.29±0.62 min) as compared to group F (7.53±2.24 min) in group B. The mean time of onset of motor block was also rapid in group B (4.13±0.78 minutes) than in group F (9.98±2.94 minutes). The mean duration of motor block was longer in group F (9.73±2.48) hours as compared to group B (7.15±2.20) hours in group A. Post-operatively at the end of 10 hours patients in group F were having discomforting pain (65%) as compared to group B who were having distressing and horrible pain (50%) as evaluated by Mc Gill pain questionnaire. Both the groups were hemodynamically stable, no side effects were noted. Conclusions: Onset of sensory and motor blockade was rapid in group B, however group F showed longer lasting motor block and postoperative analgesia. Both groups were hemodynamically stable and without any side effects.